Michael Mayfield: capstone - Mayfield, Michael, artist (Colorado State University. Libraries, 2015)
The artist's statement: How can we understand an object when the maker no longer exists? What meaning do artifacts retain when removed from their original context? These sculptures originated as African artifacts from the collection of historian Dr. David Riep. They were scanned into the computer and then carved from foam using a 3-axis CNC milling Machine. This process both removes and adds information to the surface of the objects. The original imagery is layered with incongruous materials, textures, and colors. These distorted facsimiles mock the cursory scanning of an average museum visitor. The work raises questions of art history and anthropology, by presenting a confusing and garish display of distorted sculptures, from cultures real and imagined.
I M A G E
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.